Comparative Analysis of Fiber Optic Networks Using Converter Devices with Splitters and Without Splitters in AI Building Malang State Polytechnic - Mahirani, Tika; Atmadja , Martono; Waluyo , Waluyo; Darmono , Hendro (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
A converter device is a tool for connecting copper cable network devices with fiber optic networks. This research uses a one to two splitter that connects two devices through one dropcore cable, this can reduce installation and maintenance costs. Testing in this study was carried out by measuring the power in the circuit using OPM and network speed using OpenSpeedTest software. The final result of this research is the loss calculation value and local network speed. The use of a converter device with a one to two splitter produces a loss value between 0.46 dB until 2.76 dB, while the use of a converter device without a splitter produces a loss value between 0.15 dB until 0.6 dB. The local network speed of using a converter device with a splitter shows an average PC 1 download parameter of 977.6 Mbps and 983 Mbps upload, as well as PC 2 with 977 Mbps download and 985.6 Mbps upload. While the use of a converter device without a splitter shows an average PC 1 download parameter of 977.6 Mbps and upload of 994.1 Mbps, as well as PC 2 with a download of 976.6 Mbps and upload of 995.9 Mbps.